2015
DOI: 10.1074/jbc.m115.640367
|View full text |Cite
|
Sign up to set email alerts
|

Coronin-1C Protein and Caveolin Protein Provide Constitutive and Inducible Mechanisms of Rac1 Protein Trafficking

Abstract: Background: Directional migration requires removal of Rac1 from the back of the cell.Results: Coronin-1C and caveolin provide parallel pathways for constitutive recycling or fibronectin-inducible degradation of Rac1.Discussion: Redundant trafficking pathways facilitate polarity while migrating, and responsiveness to chemotactic gradients while stationary.Significance: Maintenance of polarized migration, when the chemotactic gradient has dissipated, is essential for wound healing over a period of days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Of the five genes whose behavior most strongly mirrored that of the Yellow gene cluster as a whole, two— CORO1C and C8orf83 —are less well-studied and have not been previously associated with influenza vaccine responses. CORO1C encodes the coronin-1C protein, a member of the WD repeat protein family that is involved in a variety of cellular processes, including signal transduction and gene regulation, and may be involved in fibroblast migration 80 . C8orf83 encodes TRIQK, which is a small protein highly conserved across vertebrates with largely unknown function and may have undiscovered roles in immunity 81 .…”
Section: Discussionmentioning
confidence: 99%
“…Of the five genes whose behavior most strongly mirrored that of the Yellow gene cluster as a whole, two— CORO1C and C8orf83 —are less well-studied and have not been previously associated with influenza vaccine responses. CORO1C encodes the coronin-1C protein, a member of the WD repeat protein family that is involved in a variety of cellular processes, including signal transduction and gene regulation, and may be involved in fibroblast migration 80 . C8orf83 encodes TRIQK, which is a small protein highly conserved across vertebrates with largely unknown function and may have undiscovered roles in immunity 81 .…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, antibodies (Ab) raised against the dimerisation domain of sdc4 exhibited a blocking effect on IL-1-induced ERK signalling, but the mechanism by which the loss or inhibition of sdc4 interfered with IL1 signalling remains unclear 6. Interestingly, recent evidence suggests that trafficking of the IL-1 receptor (IL1R1) involves the formation of caveolin vesicles8 and that sdc4 may regulate the caveolin-mediated endocytosis of signalling molecules such as Rac1,9 as well as of cell surface receptors such as integrins 10…”
Section: Introductionmentioning
confidence: 99%
“…Previous work from others showed that Cav-1 modulates Rho GTPase signaling in non-neuronal cells (Baltierrez-Hoyos et al, 2012; Lim et al, 2014). Because Cav-1 has been shown to colocalize and modulate Rho GTPase activity in non-neuronal cells (Cheng et al, 2010; Bassi et al, 2011; Diaz et al, 2014; Williamson et al, 2015; Coelho-Santos et al, 2016; Xu et al, 2016), the present study tested whether Cav-1 was also involved in Rho GTPase-mediated axonal growth and neuronal differentiation in human neurons derived from induced pluripotent stem cells (iPSCs). A better mechanistic understanding of this interplay within neurons could yield potential targets for promoting functional neuroplasticity.…”
Section: Introductionmentioning
confidence: 99%